2017
DOI: 10.2217/nnm-2016-0302
|View full text |Cite
|
Sign up to set email alerts
|

Development of anti-CD47 single-chain Variable Fragment Targeted Magnetic Nanoparticles for Treatment of Human Bladder Cancer

Abstract: The anti-CD47 scFv-MNP conjugate was an effective cancer cell thermotherapy tool that might pave the way for development of bionano-based targeting techniques in both early detection and treatment of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…The expression of the cell surface integrin-associated protein CD47 (ubiquitously expressed on normal cells) is abundantly expressed on most tumor cells and creates a "do-not-eat-me" signal through binding with the signal-regulatory protein alpha (SIRPa) on macrophages (37)(38)(39). SIRPa is a regulatory membrane glycoprotein expressed on the macrophage membrane that accumulates at a phagocytic synapse between macrophages and tumor cells upon CD47 binding (37,40). Thus, the blockade of the CD47-SIRPa interaction by anti-CD47 antibody could restore the macrophagemediated phagocytosis against tumor (Figure 1) (41-43).…”
Section: Mnps For Enhancing Macrophage Anti-tumor Activitymentioning
confidence: 99%
“…The expression of the cell surface integrin-associated protein CD47 (ubiquitously expressed on normal cells) is abundantly expressed on most tumor cells and creates a "do-not-eat-me" signal through binding with the signal-regulatory protein alpha (SIRPa) on macrophages (37)(38)(39). SIRPa is a regulatory membrane glycoprotein expressed on the macrophage membrane that accumulates at a phagocytic synapse between macrophages and tumor cells upon CD47 binding (37,40). Thus, the blockade of the CD47-SIRPa interaction by anti-CD47 antibody could restore the macrophagemediated phagocytosis against tumor (Figure 1) (41-43).…”
Section: Mnps For Enhancing Macrophage Anti-tumor Activitymentioning
confidence: 99%
“…[197,[375][376][377][378][379][380][381] Rezaei et al synthesized an anti-CD47 scFv through an immunized antibody phage display library and then conjugated the selected scFvs to magnetic nanoparticles (forming scFv-MNPs). [382] The scFv-MNPs displayed high affinity toward CD47-positive bladder cancer cells, enabling significant inhibition of tumor growth and metastasis in animal models. Besides, Zou et al demonstrated that the NPs functionalized by svFc fragments could be used as theranostic agents for the detection and treatment of pancreatic cancer.…”
Section: Nanoparticles Functionalized By Single-chain Variable Fragme...mentioning
confidence: 99%
“…While the wealth of information in terms of production and modification often favors the use of full antibodies for targeting purposes, limitations such as immunogenicity, low stability, rapid elimination, and less than expected efficiency have promoted the generation and use of various antibody fragments [ 287 ]. Within this context, Fab type fragments [ 288 ], single chain variable fragments (scfV) [ 289 ], half-antibodies (hAB) [ 290 ], diabodies [ 291 ], and bispecific antibodies [ 292 ] have been tagged on nanoparticle surface to enhance their specificity for a certain target. Antibody fragments are advantageous over full immunoglobulins in terms of their lower immunogenicity, higher nanoparticle loading due to their smaller size, and better controllability of their orientation on the nanoparticle surface [ 287 ].…”
Section: Active Targetingmentioning
confidence: 99%